Pendidikan Karakter Guru PAI dalam Tafsir al-Ibriz - Bayu Mujrimin (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to examine the character education of Islamic Religious Education (IRE) teachers through the understanding of the values of sincerity (ikhlas) and trustworthiness (amanah) as presented in Tafsir al-Ibriz by K.H. Bisri Mustofa. In the context of teacher professionalism, these two values are foundational pillars that shape integrity and exemplary conduct in education. Using a qualitative approach based on library research and thematic interpretation analysis, this study finds that sincerity in Tafsir al-Ibriz is interpreted as pure devotion to Allah without expecting worldly rewards, while trustworthiness is understood as a moral and spiritual responsibility in fulfilling educational duties. These values play a crucial role in shaping teachers who are not only pedagogically competent but also possess high moral integrity. The findings of this study are expected to contribute to the development of character education for IRE teachers that is contextual and rooted in classical Islamic values.